2012
DOI: 10.1111/j.1742-4658.2012.08722.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of identity elements on the aminoacylation of tRNAArg by plant and Escherichia coli arginyl‐tRNA synthetases

Abstract: Identity elements determine the accurate recognition between tRNAs and aminoacyl-tRNA synthetases. The arginine system from yeast and Escherichia coli has been studied extensively in the past. However, information about the enzymes from higher eukaryotes is limited and plant aminoacyltRNA synthetases have been largely ignored in this respect. We have designed in vitro tRNA transcripts, based on the soybean tRNA Arg primary structure, aiming to investigate its specific aminoacylation by two recombinant plant ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 60 publications
(104 reference statements)
0
13
0
Order By: Relevance
“…Research on plant aaRSs revealed their cellular localization (Rokov-Plavec et al 2008, Duchêne et al 2009, Kekez et al 2016, substrate specificity (Rokov et al 2008, Rokov and Weygand-Durasevic 2009, Rokov-Plavec et al 2002, 2004, Aldinger et al 2012, fidelity (Rokov-Plavec et al 2013, Lee et al 2016, Hoffman et al 2019 and protein interactors (Yang et al 2018, Kekez et al 2019. Thus far, only one crystal structure of plant aaRS is reported (Kekez et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Research on plant aaRSs revealed their cellular localization (Rokov-Plavec et al 2008, Duchêne et al 2009, Kekez et al 2016, substrate specificity (Rokov et al 2008, Rokov and Weygand-Durasevic 2009, Rokov-Plavec et al 2002, 2004, Aldinger et al 2012, fidelity (Rokov-Plavec et al 2013, Lee et al 2016, Hoffman et al 2019 and protein interactors (Yang et al 2018, Kekez et al 2019. Thus far, only one crystal structure of plant aaRS is reported (Kekez et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of arginyl‐tRNA synthetase, the enzyme from Escherichia coli requires nucleotide A20 as a major identity element in tRNA and is unable to arginylate the corresponding yeast tRNA that possesses C20 , although the yeast enzyme recognizes the bacterial tRNA. Extrapolating this observation to the Cyto / Mito system, it is well‐established that the Cyto arginyl‐tRNA synthetase in mammals and plants relies on the presence of A20 . Conversely, Coleopteran Mito tRNA Arg lacks a canonical A20 base and is not aminoacylated by the (Cyto‐like) E. coli enzyme .…”
Section: Resultsmentioning
confidence: 93%
“…However, neither was a substrate for a higher eukaryotic (plant) cytoplasmic arginyl-tRNA synthetase (data not shown) that requires an A20 identity element. 43 Parenthetically, evidence has been presented that the yeast cytoplasmic arginyltRNA synthetase has mitochondrial origins. 53,54 Finally, in a third class of sponges, the Calcarea, the CGN arginine codon has been reassigned to glycine, retaining tRNA Arg UCU as the sole arginine decoder.…”
Section: Discussionmentioning
confidence: 98%
“…The identity elements are independent of the sequence of the distal acceptor stem. The major identity element A20, that has been described for the E.coli, 44 mammalian cytoplasmic 45 and plant arginyltRNA synthetases, 43 has been lost in insect mitochondria during the evolution of highly variable and, in some species, rudimentary D-stem/loops. The activity of the C. duodecimpunctata tRNA Ala whose anticodon had been replaced by UCG supports the conclusion that the discriminator base U 73 (tRNA Arg ) or A 73 (tRNA Ala ) does not play a role in recognition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation